DIAGNOSTIC ACCURACY OF NON-INVASIVE MARKERS (FIB 4, APRI AND GALL BLADDER WALL THICKNESS) IN DIAGNOSIS OF ESOPHAGEAL VARICES (The Research of Medical Science Review, 2025)
Background: Esophageal varices are a common and potentially life-threatening complication of liver cirrhosis. Early detection and monitoring are essential for managing cirrhotic patients and preventing variceal bleeding. Invasive procedures such as endoscopy, while accurate, are not feasible for routine screening. Noninvasive markers like FIB-4, APRI, and gallbladder wall thickness (GBWT) offer potential alternatives for diagnosing esophageal varices. Objective: To evaluate the diagnostic accuracy of non-invasive markers (FIB-4, APRI, and GBWT) in predicting esophageal varices, using endoscopy as the gold standard. Study Design & Setting: This cross-sectional study was conducted at the Department of Medicine, Chaudhary Muhammad Akram Teaching Hospital & Research Center, Lahore from 2 February 2024 to 2 August 2024. Methodology: A total of 115 cirrhotic patients aged 15–75 years were enrolled using non-probability consecutive sampling. Demographic data, medical history, and laboratory findings (AST, ALT, platelet count) were recorded. FIB-4 and APRI scores were calculated, and gallbladder wall thickness was measured through ultrasound. Endoscopy was performed to detect esophageal varices. Diagnostic accuracy was evaluated through sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Data analysis was performed using SPSS version 25.0. Results: The diagnostic accuracy of the FIB-4 score was 66.1% with a sensitivity of 72.1% and specificity of 60.3%. The APRI score demonstrated an accuracy of 66.9%, sensitivity of 69.7%, and specificity of 62.5%. Gallbladder wall thickness showed an accuracy of 66.1%, sensitivity of 75.0%, and specificity of 58.8%. Among the three markers, FIB-4 demonstrated the highest overall accuracy, while GBWT exhibited the highest sensitivity. reasonable diagnostic accuracy in predicting esophageal varices, offering a useful screening alternative to endoscopy. Further large-scale studies are recommended to validate these findings.Conclusion: Non-invasive markers, particularly the FIB-4 score, demonstrate